Management of Ramularia leaf spot on cotton using integrated control with genotypes, a fungicide and Trichoderma asperellum - Silva, Juliano Cesar da [UNESP]; Suassuna, Nelson Dias; Bettiol, Wagner (Elsevier B.V., 2017)
Ramularia leaf spot, caused by Ramularia areola, is responsible for premature defoliation of cotton, resulting in potential reductions in yield. The objective of this study was to evaluate integrated control using genotypes, a fungicide and Trichoderma asperellum to manage Ramularia leaf spot on cotton. In the greenhouse, the resistance of eighteen genotypes was evaluated with two isolates of R. areola (IMA 244 and IMA 237). In field, the severity of Ramularia leaf spot was evaluated on cotton genotypes CNPA MT 2009-1381, CNPA GO 2007-419, BRS 293, BRS 372, CNPA GO 2008-1265 and FMT 701 treated or untreated with a fungicide in Primavera do Leste, MT, Correntina, BA, and Santa Helena de Goias, GO, during the 2011-2012 season. The varieties BRS 293 and BRS 372 were sprayed with a fungicide or Trichoderma in Sapezal, MT, during the 2012-2013 season, and the disease severity and fiber yield were evaluated. Significant interactions were detected between Ramularia isolates and cotton genotypes; the lowest disease severity was observed with IMA CD 05-8276 and CNPA GO 2007-419 genotypes. In the field tests, the lowest disease severity was with variety BRS 372 and the highest was with BRS 293, when grown in two different regions. The chemical fungicide and T. asperellum both reduced the disease severity in cotton varieties BRS 372 and BRS 293; however, yields were not significantly affected. In conclusion, an integrated strategy with the management tools of resistant varieties, fungicides and biocontrol agents should be used to control Ramularia leaf spot on cotton. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Cotton varieties; Gossypium hirsutum; Ramularia areola; Ramularia leaf spot; Biological control